Liquid chromatography/mass spectrometry based detection and semi‐quantitative analysis of INSL5 in human and murine tissues. (6th November 2017) - Kay, R.G.; Galvin, S.; Larraufie, P.; Reimann, F.; Gribble, F.M.
Abstract : Rationale: Insulin‐like peptide 5 (INSL5) is a hormone produced by enteroendocrine L‐cells in the colon that has recently been implicated in the control of metabolic homeostasis. However, research into its physiology has been hindered by the reported unreliability of commercially available immunoassays and additional detection assays would benefit this emerging field. Methods: Peptides from purified murine L‐cells and homogenates from both human and mouse colonic tissues were extracted by precipitating larger proteins with acetonitrile. Untargeted liquid chromatography/tandem mass spectrometry (LC/MS/MS) analyses, followed by database searching, were used to detect and identify various INSL5 gene derived peptides and characterise their precise sequence. A similar approach was developed to quantify INSL5 levels in primary intestinal culture supernatants after purification and concentration by solid‐phase extraction. Results: Mass spectral analysis of purified enteroendocrine cells and tissue homogenates identified the exact sequence of A and B chains of INSL5 endogenously expressed in L‐cells. Differences in the endogenously processed peptide and the Swissprot database entry were observed for murine INSL5, whereas the human sequence matched previous predictions from heterologous expression experiments. INSL5 was detected in the supernatant of human and mouse primary colonic cultures and concentrations increased after treatment with a known L‐cell stimulus. Conclusions: The first LC/MS/MS‐based method capable of the detection and semi‐quantitative analysis of endogenous INSL5 using MS‐based techniques has been demonstrated. The methodology will enable the identification of stimulants for INSL5 secretion from murine and human primary colonic epithelial cultures.